Explore Westonci.ca, the top Q&A platform where your questions are answered by professionals and enthusiasts alike. Connect with professionals on our platform to receive accurate answers to your questions quickly and efficiently. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.

Find the 57th term of the sequence:

Given sequence: [tex]\(13, 8, 3, -2, -7, -12, \ldots\)[/tex]

1. Enter the common difference:

[tex]\[ \text{common difference} = 8 - 13 \][/tex]

2. Use the formula for the [tex]\(n\)[/tex]-th term of an arithmetic sequence:

[tex]\[ a_n = a_1 + (n-1)d \][/tex]

3. Find the 57th term:

[tex]\[ a_{57} = 13 + (57-1)(-5) \][/tex]


Sagot :

To find the 57th term of the given arithmetic sequence, we start by identifying the components of the sequence:

1. The first term ([tex]\(a\)[/tex]) is [tex]\(13\)[/tex].
2. The common difference ([tex]\(d\)[/tex]) is calculated as [tex]\(3 - 8 = -5\)[/tex].

The formula to find the [tex]\(n\)[/tex]th term ([tex]\(a_n\)[/tex]) of an arithmetic sequence is:
[tex]\[ a_n = a + (n - 1) \cdot d \][/tex]

Let's plug in the values:
- [tex]\(a = 13\)[/tex] (the first term)
- [tex]\(d = -5\)[/tex] (the common difference)
- [tex]\(n = 57\)[/tex] (the position of the term we want to find)

Substitute these values into the formula:
[tex]\[ a_{57} = 13 + (57 - 1)\cdot (-5) \][/tex]

Simplify the expression inside the parentheses:
[tex]\[ a_{57} = 13 + 56 \cdot (-5) \][/tex]

Now, multiply [tex]\(56\)[/tex] by [tex]\(-5\)[/tex]:
[tex]\[ 56 \cdot (-5) = -280 \][/tex]

Add this result to the first term:
[tex]\[ a_{57} = 13 + (-280) \][/tex]

This simplifies to:
[tex]\[ a_{57} = 13 - 280 = -267 \][/tex]

So, the common difference is [tex]\(-5\)[/tex], and the 57th term of the sequence is [tex]\(-267\)[/tex].